2021
DOI: 10.1029/2021ja029353
|View full text |Cite
|
Sign up to set email alerts
|

ULF‐Modulation of Whistler‐Mode Waves in the Inner Magnetosphere During Solar Wind Compression

Abstract: The solar wind plays important roles in terrestrial magnetosphere dynamics, including the particle population and plasma wave generation. Here, we report an interesting event that ultralow frequency (ULF) waves are enhanced right after solar wind compression and the compressional mode ULF wave subsequently modulates both the intensity and energy flux direction of whistler‐mode waves. Quasi‐periodic whistler‐mode wave packets are observed around L = 5.6 at noon sector by Van Allen Probes. Growth rate calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In fact, the observed modulation of the chorus waves by ULF compressional waves was interpreted in Shang et al. (2021) as the chorus wave source region being modified by the north/south oscillations of the magnetic flux tubes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, the observed modulation of the chorus waves by ULF compressional waves was interpreted in Shang et al. (2021) as the chorus wave source region being modified by the north/south oscillations of the magnetic flux tubes.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, the excitation of the chorus waves may be modulated by the large-scale ULF waves via regulating the background field configurations. In fact, the observed modulation of the chorus waves by ULF compressional waves was interpreted in Shang et al (2021) as the chorus wave source region being modified by the north/south oscillations of the magnetic flux tubes.…”
mentioning
confidence: 99%
“…ULF waves can also modulate higher-frequency, EMIC and VLF wave growth (e.g., Li et al, 2011;Gamayunov and Engebretson, 2021;Shang et al, 2021), transferring energy from large to small scales. Concerning EMIC waves, the pioneering work by Lyons and Thorne (1972) demonstrated that these waves can play a critical role in the dynamics of multi-MeV electrons.…”
Section: How Do Ulf Waves Couple To the Radiation Belts?mentioning
confidence: 99%
“…Previous studies suggest that the whistler‐mode chorus waves are generally intensified (Fu, Cao, Mozer, et al., 2012; Fu, Cao, Zong, et al., 2012), while the intensity of plasmaspheric hiss waves decreases in the dayside and increases in the nightside (Liu, Su, Gao, Reeves, et al., 2017; Su et al., 2015; Yue et al., 2017) after the IP shock arrival. More recent studies indicate that plasmaspheric hiss waves also show patchy or modulated patterns under disturbed solar wind conditions or IP shock arrival (Chakraborty et al., 2021; Liu et al., 2019; Shang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%